An Assessment of Genetic Counseling Services for Individuals with Multiple Sclerosis. Issue 1 (5th July 2014) - Skinner, Stephanie; Guimond, Colleen; Butler, Rachel; Dwosh, Emily; Traboulsee, Anthony L.; Sadovnick, A. Dessa
Abstract: Multiple sclerosis (MS) affects up to 1/500 Canadians. The University of British Columbia MS Clinic (UBC Clinic) is the only MS clinic in Canada (and likely internationally) that routinely offers genetic counseling to patients and their families. A typical session includes the collection of family history and demographic data, discussion of the inheritance of MS, interpretation of family‐specific recurrence risks and psychosocial counseling. The aims of this study were to explore patients': 1) expectations of the genetic counseling session; 2) understanding of the etiology of MS (both pre and post‐session); and 3) post‐session perceptions of genetic counseling. A two‐part questionnaire to assess genetic counseling services was distributed before and after sessions to all consenting patients seen during the period October 1, 2008 to February 28, 2009 inclusive. Sixty‐two completed questionnaires were analysed. Genetic counseling was found to significantly increase the number of individuals who were able to correctly identify the etiology of MS ( p  < 0.001). Patient satisfaction with genetic counseling was high, with an average satisfaction score of 32.4/35 (92.6 %). Of those who provided comments ( n  = 42/60) regarding the usefulness of the genetic counseling session, 95.2 % reported it useful ( n  = 40/42). Findings suggest that genetic counseling is effective in increasing patients' knowledge of the etiology of MS and is viewed by patients as a useful service. Based on the high level of positive feedback regarding genetic counseling by the study sample, this study suggests that the services provided by genetic counselors may be beneficial for patients with MS seen in other centers.